Induced Hypothermia Does Not Harm Hemodynamics after Polytrauma: A Porcine Model. (11th June 2015) - Weuster, Matthias; Mommsen, Philipp; Pfeifer, Roman; Mohr, Juliane; Ruchholtz, Steffen; Flohé, Sascha; Fröhlich, Matthias; Keibl, Claudia; Seekamp, Andreas; van Griensven, Martijn; Witte, Ingo
Abstract : Background . The deterioration of hemodynamics instantly endangers the patients' life after polytrauma. As accidental hypothermia frequently occurs in polytrauma, therapeutic hypothermia still displays an ambivalent role as the impact on the cardiopulmonary function is not yet fully understood. Methods . We have previously established a porcine polytrauma model including blunt chest trauma, penetrating abdominal trauma, and hemorrhagic shock. Therapeutic hypothermia (34°C) was induced for 3 hours. We documented cardiovascular parameters and basic respiratory parameters. Pigs were euthanized after 15.5 hours. Results . Our polytrauma porcine model displayed sufficient trauma impact. Resuscitation showed adequate restoration of hemodynamics. Induced hypothermia had neither harmful nor major positive effects on the animals' hemodynamics. Though heart rate significantly decreased and mixed venous oxygen saturation significantly increased during therapeutic hypothermia. Mean arterial blood pressure, central venous pressure, pulmonary arterial pressure, and wedge pressure showed no significant differences comparing normothermic trauma and hypothermic trauma pigs during hypothermia. Conclusions . Induced hypothermia after polytrauma is feasible. No major harmful effects on hemodynamics were observed. Therapeutic hypothermia revealed hints for tissue protective impact. But the chosen length for therapeutic hypothermia was too short. Nevertheless, therapeutic hypothermia might be a useful tool for intensive care after polytrauma. Future studies should extend therapeutic hypothermia.